Does a connection exist among national culture, alliance strategy, and leading ICT firms’ performance? - Golonka, Monika; Rzadca, Robert (Journal of Business Economics and Management, 2013)
In this paper we explore links among firms’ performance, firms’ alliance strategies, and national culture in the context of the global information and communication technologies (ICT) industry. Currently, partnering is the one of the most effective ways to access a broad set of resources. In the ICT industry, we can observe a significant number of alliances, networks, and mergers and acquisitions. The contribution of this paper is to investigate how a contextual factor – namely, national culture – influences the alliance portfolio formation and a firm’s performance. We also aim to contribute to the issue of alliance portfolio formation. First, the concepts of alliance portfolio and culture as an explanatory factor are elaborated upon and their relevance to the study discussed. Second, using a sample of 30 ICT leaders and 10,247 of their alliances, we explore the effect of alliance strategy on firms’ performance as well as the connections among culture, firms’ performance, and alliance strategy. The study confirms that, in a global ICT industry (i.e., the most dynamically changing and riskiest environment), weak alliances may increase a firm’s performance more than strong, traditional strategic alliances. Culture may be used as one of the explanatory factors affecting firms’ performance as well as firms’ alliance strategies.Reference to this paper should be made as follows: Golonka, M.; Rzadca, R. 2013. Does a connection exist among national culture, alliance strategy, and leading ICT firms’ performance?, Journal of Business Economics and Management 14(Supplement 1): S395–S412.